Simultaneous Singlet-Singlet and Triplet-Singlet Forster Resonance Energy Transfer from a Single Donor Material - Kirch, Anton; Gmelch, Max; Reineke, Sebastian (Journal of Physical Chemistry Letters, 2019)
For almost 70 years, Forster resonance energy transfer (FRET) has been investigated, implemented into nowadays experimental nanoscience techniques, and considered in a manifold of optics, photonics, and optoelectronics applications. Here, we demonstrate for the first time simultaneous and efficient energy transfer from both donating singlet and triplet states of a single photoluminescent molecular species. Using a biluminescent donor that can emit with high yield from both excited states at room temperature allows application of the FRET framework to such a bimodal system. It serves as an exclusive model system where the spatial origin of energy transfer is exactly the same for both donating spin states involved. Of paramount significance are the facts that both transfers can easily be observed by eye and that Forster theory is successfully applied to state lifetimes spanning over 8 orders of magnitude.